Impact of blade direction on postoperative femoral head varus in PFNA fixed patients: a clinical review and biomechanical research - Xu, Yue; Zhang, Xiaoyu; Li, Jingchi; Miao, Yiming; Ying, Pu; Chen, Cong; Xu, Wenqiang; Wang, Qiang (Frontiers in Bioengineering and Biotechnology, 2024)
Intertrochanteric femur fracture is a common type of osteoporotic fracture in elderly patients, and postoperative femoral head varus following proximal femoral nail anti-rotation (PFNA) fixation is a crucial factor contributing to the deterioration of clinical outcomes. The cross-angle between the implant and bone might influence fixation stability. Although there is a wide range of adjustment in the direction of anti-rotation blades within the femoral neck, the impact of this direct variation on the risk of femoral head varus and its biomechanical mechanisms remain unexplored. In this study, we conducted a retrospective analysis of clinical data from 69 patients with PFNA fixation in our institution. We judge the direction of blade on the femoral neck in on the immediate postoperative lateral X-rays or intraoperative C-arm fluoroscopy, investigating its influence on the early postoperative risk of femoral head varus. P < 0.05 indicates significant results in both correlation and regression analyses. Simultaneously, a three-dimensional finite element model was constructed based on the Syn-Bone standard proximal femur outline, exploring the biomechanical mechanisms of the femoral neck-anti-rotation blade direction variation on the risk of this complication. The results indicated that ventral direction insertion of the anti-rotation blade is an independent risk factor for increased femoral head varus. Complementary biomechanical studies further confirmed that ventral angulation leads to loss of fixation stability and a decrease in fixation failure strength. Therefore, based on this study, it is recommended to avoid ventral directional insertion of the anti-rotation blade in PFNA operation or to adjust it in order to reduce the risk of femoral head varus biomechanically, especially in unstable fractures. This adjustment will help enhance clinical outcomes for patients.